Dissecting the functions of conserved prolines within transmembrane helices of the D2 dopamine receptor - Arnam, Ethan B. Van (2011)
G protein–coupled receptors (GPCRs) contain a number of conserved proline residues in their transmembrane helices, and it is generally assumed these play important functional and/or structural roles. Here we use unnatural amino acid mutagenesis, employing α–hydroxy acids and proline analogs, to examine the functional roles of five proline residues in the transmembrane helices of the D2 dopamine receptor. The well–known tendency of proline to disrupt helical structure is important at all sites, while we find no evidence for a functional role for backbone amide cis–trans isomerization, another feature associated with proline. At most proline sites, the loss of the backbone NH is sufficient to explain the role of the proline. However, at one site – P210(5.50) – a substituent on the backbone N appears to be essential for proper function. Interestingly, the pattern in functional consequences that we see is mirrored in the pattern of structural distortions seen in recent GPCR crystal structures.